Numerical Simulation of Galloping Characteristics of Multi-Span Iced Eight-Bundle Conductors Tower Line System - Bowen Tian; Mengqi Cai; Linshu Zhou; Hanjie Huang; Shunli Ding; Junhao Liang; Maoming Hu (Buildings, 2022)
The galloping condition of an iced eight-bundle conductor tower line system, under different parameters, is studied by using a finite element model of a multi-span iced eight-bundle conductor tower line system. The galloping frequency, amplitude, traces of multi-span iced eight-bundle conductors under different wind velocities, span lengths, and initial angles of wind attack are discussed. The different tower line connection methods are compared, based on existing research on the relationship between the aerodynamic characteristics of the conductor and galloping conditions. The results show that the galloping situation of a multi-span iced eight-bundle conductor tower line system varies greatly depending on the conditions, which has a significant impact on the tower line.